Coding Theory Recent Advances, New Perspectives and Applications - Radhakrishnan, Sudhakar; Naduvath, Sudev (IntechOpen, 2022)
This book explores the latest developments, methods, approaches, and applications of coding theory in a wide variety of fields and endeavors. It consists of seven chapters that address such topics as applications of coding theory in networking and cryptography, wireless sensor nodes in wireless body area networks, the construction of linear codes, and more.